METODE PEMBELAJARAN TEMATIK DAN PENDIDIKAN AGAMA ISLAM BAGI SISWA TUNARUNGU - Ischak Suryo Nugroho; Wilda Fazmi Luvita; Muh. Hanif Muh. Hanif (Mozaic : Islam Nusantara, 2021)
The learning method is a method used by teachers to deliver material and manage learning activities so that students can learn to achieve the expected learning objectives. The ability of students is one of the considerations for selecting learning methods. Difficulty listening or hearing impairment experienced by students tends to result in difficulty speaking or communicating verbally. This also has a negative impact on the ability to understand the subject matter. This paper is based on a qualitative study of students with hearing difficulties (deaf) in grade IV at SDLB-B in Purwokerto. Data were collected through observation, interviews, and documentation. The invormants studied were 20 students by practicing the gender balance of 10 girls and 10 boys. Panelitan data were analyzed using Miles and Huberman models, namely Data Reduction, Data Display, and Verification. The results showed that SDLB-B in Purwokerto used the 2013 curriculum, learning was carried out thematically. To get around the inability of deaf students to communicate, hear and have difficulty understanding the subject matter, the teacher chooses various learning methods that aim to make deaf students receive and capture the content of the subject matter correctly and optimally and can improve language competence. Thematic learning in various subjects for deaf grade IV students at SDLB-B Purwokerto uses various general methods that can be used for both general students and students with special needs, namely the lecture method, question and answer method, discussion, drill (exercise), recitation (assignment), and demonstration. In applying these methods the teacher always combines it with speech therapy methods for deaf students such as the SIBI (Indonesian Language Signaling System) method, the lips reading method (reading lips), and the Maternal Reflective Method (MMR).